Multiple waves of colonization by monarch flycatchers ( Myiagra , Monarchidae) across the Indo‐Pacific and their implications for coexistence and speciation - Pierre‐Henri Fabre; Maria Moltensen; Jon Fjeldså; Martin Irestedt; Jean‐Philippe Lessard; Knud A. Jønsson (Journal of Biogeography, 2014)
Aim Islands and archipelagos have played an important role in the development of ecological and evolutionary theories. Using a newly compiled molecular phylogeny we infer the biogeographical history of a monarch flycatcher genus, M yiagra , which is distributed across the Indo‐Pacific. We subsequently integrate biogeographical and ecomorphological data to examine the role of dispersal and trait evolution in the build‐up of avian assemblages. Location Australia, the Moluccas, New Guinea and Pacific islands. Methods We generated a taxonomically densely sampled mitochondrial DNA dataset that included almost all species and subspecies of the reciprocally monophyletic genera Myiagra and Arses . We then used maximum likelihoood and Bayesian inference to infer their phylogenetic relationships. To reconstruct their biogeographical history, we first dated the tree topology and then used Lagrange to infer ancestral geographical areas. Finally, we combined ancestral area reconstructions with information on ecomorphological traits to infer mechanisms underlying community assembly. Results We provide the first comprehensive molecular phylogenetic reconstruction for Myiagra and Arses monarch flycatchers. Our phylogenetic reconstruction reveals a relatively recent diversification from the Miocene associated with several major dispersal events. Ancestral area reconstruction reveals several independent colonizations of the Moluccas, Melanesia, Fiji and the Micronesian islands. Ancestral state reconstruction of ecological traits suggests that the diversity of traits in co‐occurring species of monarch flycatchers results from independent colonization events and ecological niche conservatism rather than in situ diversification. Main conclusions Three waves of colonization, non‐overlapping in time, led to independent speciation events in the Bismarcks, Fiji and the Moluccas, in addition to in situ speciation events on remote islands of Micronesia, the Solomons, Vanuatu and Samoa. Few of these colonizations have led to the co‐occurrence of congenerics or species with similar ecomorphological profiles on the same island. Thus, we suggest that priority effects might prevent new colonizers from establishing themselves if they share high levels of ecological similarity with resident species. We conclude that historical dispersal to and colonization of new islands, combined with ecologically deterministic priority effects, drove the assembly of insular monarch flycatcher communities across the Indo‐Pacific.